Optimizing Economic Outcomes Through Information System Utilization: Enhancing Competency in Civil Servant Candidate Basic Training at South Sulawesi - Jamaluddin, Hamdana (Yayasan Riset dan Pengembangan Intelektual, 2024)
System (LMS) in supporting competency development among Civil Service Candidates (CPNS) at the Human Resource Development Agency (BPSDM) in South Sulawesi Province. Using a mixed-methods approach, the research combines quantitative surveys of 89 CPNS participants with qualitative interviews of 20 participants to assess SIBANG’s impact on technical, managerial, and socio-cultural competencies. Quantitative results indicate that while SIBANG effectively supports technical competency development, the platform is less effective in enhancing managerial and socio-cultural skills, which require more interactive and hands-on learning methods. The regression analysis shows a positive but statistically insignificant relationship between SIBANG usage frequency and competency improvement, suggesting that additional factors, such as content interactivity and technical infrastructure, play a critical role. Qualitative findings highlight challenges such as connectivity issues, usability concerns, and a need for more practical learning tools within SIBANG. Based on these insights, the study recommends incorporating interactive features, enhancing technical support, and providing targeted guidance to optimize SIBANG’s potential as a comprehensive training tool. These improvements could enable SIBANG to better support the diverse competency needs of CPNS, contributing to the development of a skilled and adaptable civil service workforce.